PEMBERDAYAAN PEREMPUAN SEBAGAI KEPALA KELUARGA DALAM KONSTRUK SOSIAL RUMAH TANGGA - Kadir, Musyarrafah Abdul (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2023)
The concept of gender in Islam does not differentiate between the sexes of males and females. Women and men play crucial roles in every aspect of life, particularly as spouses cooperating in navigating the dynamics of household life. The purpose of this writing is to describe that women, especially as wives with dual roles as heads of the family, are capable of empowering themselves and their children, as well as revitalizing family functions for the sake of well-being, tranquility, and harmony within their households. This study employs a qualitative descriptive method using library research, focusing on gathering data and facts related to the research topic and analyzing the data descriptively. The results of this study conclude that women are capable of playing roles beyond their traditional roles as homemakers; they can act as household heads. Empowering women as household heads is a manifestation of their self-reliance and personal capability in addressing the issues within their households amidst their busy schedules of caring for their children, aiming for the continuity of life and the welfare of their families.